MENELISIK PERAN TATA KELOLA PERUSAHAAN DAN KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ida Ayu Ratih Manuari; Ni Luh Nyoman Sherina Devi (Universitas Triatma Mulya, 2023)
Financial distress is a condition or condition of a company that is experiencing financial difficulties, is insecure and is threatened with bankruptcy. The purpose of this study is to test and obtain empirical evidence regarding the implications of the roles of managerial ownership, institutional ownership, independent commissioners, board of directors, liquidity, leverage and profitability in the financial distress of manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2019 period. There were 24 manufacturing companies that were sampled in this study with a total observation time of 3 years so that the total sample for this study was 72 which were determined based on the purposive sampling method. The logistic regression analysis technique became a hypothesis testing technique in this study. From the test results it was found that managerial ownership, institutional ownership, independent commissioners, board of directors, liquidity, leverage have no effect on financial distress, profitability has a negative effect on financial distress. The implication of this research is to clarify the need for procurement of evaluation and analysis for a company in implementing a strategy that will affect the emergence of potential financial difficulties or financial distress. This will prevent the company from going bankrupt in the future